Study of Soil Erosion Risk in the Basin of Northern Al-Kabeer River in Lattakia using Remote Sensing and Geographic Information System (GIS) Techniques (Global Journal of Science Frontier Research, 2015)
Abstract not found
Keywords: risk water erosion; geographic information system; Al-Kabeer northeren river; CORINE methodology